Dataset with the experiences on integrated landscape management across Latin America and the Caribbean - Estrada-Carmona, Natalia (2020)
The dataset contains the characterization of 104 integrated landscape initiatives surveyed in 2012. The survey questionnaire included a combination of closed and open-ended questions oriented to solicit information on the initiatives’ location and context, motivations and impetus, participants and stakeholders, investments and governance structures, outcomes, and most and least successful aspects. The questions were designed to gather information on the investments and outcomes of landscape initiative in four key activity domains: agriculture, conservation, livelihoods, and institutional planning and coordination. The dataset with the close-ended questions is made available to enable more comprehensive analysis and facilitating collaboration between initiatives and researchers (or institutions) interested in landscape-level planning, integrated landscape approach, and sustainable development. Open-ended questions are available in Spanish and Portuguese and upon request. You can find an approximate location of the initiatives here: https://worldmap.harvard.edu/maps/ILIs_LAC/bBV. (2020-01-14)